2005
DOI: 10.1271/bbb.69.1403
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Immunity Protein, NukH, for the Lantibiotic Nukacin ISK-1 Produced byStaphylococcus warneriISK-1

Abstract: Staphylococcus warneri ISK-1 produces a lantibiotic, nukacin ISK-1. The nukacin ISK-1 gene cluster consists of at least six genes, nukA, -M, -T, -F, -E, and -G, and two open reading frames, ORF1 and ORF7 (designated nukH). Sequence comparisons suggested that NukF, -E, -G, and -H contribute to immunity to nukacin ISK-1. We investigated the immunity levels of recombinant Lactococcus lactis expressing nukFEG and nukH against nukacin ISK-1. The co-expression of nukFEG and nukH resulted in a high degree of immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 23 publications
0
81
0
Order By: Relevance
“…Plasmid pNZ8048 was used for the expression of nukF, nukE, nukG, and nukH. The methods of constructing pNZFEGH, pNZFEG, and pNZH, which are pNZ8048 derivatives containing nukFEGH, nukFEG, and nukH, respectively, have been described previously (3). The nukF gene in pNZFEGH was inactivated by digestion with the restriction enzymes BstZ17I and BsaI.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Plasmid pNZ8048 was used for the expression of nukF, nukE, nukG, and nukH. The methods of constructing pNZFEGH, pNZFEG, and pNZH, which are pNZ8048 derivatives containing nukFEGH, nukFEG, and nukH, respectively, have been described previously (3). The nukF gene in pNZFEGH was inactivated by digestion with the restriction enzymes BstZ17I and BsaI.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of nukacin ISK-1 is believed to be formed by the N-terminal tail region (positions 1 to 7) and the C-terminal ring region, containing unusual amino acids (positions 7 to 27) (2). The self-protection system against nukacin ISK-1 is conferred by the LanFEG-type protein NukFEG and a novel type of lantibiotic-binding immunity protein, NukH (3,4). Previously, we demonstrated that expression of nukFEG and nukH increases the immunity level of a nukacin ISK-1-sensitive Lactococcus lactis strain and that expression of both is required for full immunity (3).…”
mentioning
confidence: 99%
See 3 more Smart Citations